A new species of upland Stream Toad of the genus Ansonia Stoliczka, 1870 (Anura: Bufonidae) from northeastern Peninsular Malaysia - Chan, Kin Onn; Wood Jr, Perry L.; Anuar, Shahrul; Muin, Mohd Abdul; Quah, Evan S.h.; Sumarli, Alexandra X. Y. (Zootaxa, 2014)
A new species of Ansonia is described based on genetic and morphological differentiation. Ansonia lumut sp. nov. is most closely related to three other Peninsular Malaysian species, A. penangensis, A. malayana, and A. jeetsukumarani but differs from these and other congeners by at least 6.9% sequence divergence at the 12S, 16S rRNA and t-RNA-val genes and the following combination of morphological characters: (1) SVL 21.0–23.6 mm in males, 27.7–31.6 mm in females; (2) first finger shorter than second; (3) interorbital and tarsal ridges absent; (4) light interscapular spot absent; (5) presence of large, yellow rictal tubercle; (6) dorsum black with greenish-yellow reticulations; (7) flanks with small yellow spots; (8) fore and hind limbs with yellow cross-bars; and (9) venter light gray with fine, white spotting.